The Influence of First-Line Manager Supervision on Nurse Competence in Discharge Planning Implementation at X Hospital Medan - Rosita Lumban Gaol; Dwi Hapsari Tjandrarini; Asnet Leo Bunga (Interdisciplinary Social Studies, 2025)
First-line managers have an important role in supervision to improve performance and quality of nursing services. This study aims to determine the effect of first-line manager supervision on nurse competence in the implementation of discharge planning. The research method used was quasi-experiment pre-test and post-test nonequalent control group. The number of samples was 70 executive nurses who were divided into an intervention group in Medan X Hospital and a control group in RS. XX TB Simatupang, taken with sequential sampling strategy. Data was collected using a valid and reliable supervision questionnaire. The results showed that there were differences in nurse competence scores in the implementation of discharge planning p=0.000 and supervision of first-line managers p=0.000 before and after supervision training. The results of the logistic regression test showed that there were three variables most influential on nurse competence in implementing discharge planning, namely age (p=0.010), length of work (p=0.004) and level of education (p=0.032). Conclusion: supervision of first-line managers has an important role in improving nurse competence in implementing discharge planning. Suggestions for the nursing division to conduct routine evaluations of the implementation of discharge planning, standardise first-line manager supervision instruments and the need to monitor and evaluate supervision of supervision and completeness of discharge planning documents.